FAKTOR YANG BERHUBUNGAN DENGAN PRAKTEK VAKSINASI COVID-19 PADA MASYARAKAT DI WILAYAH KERJA PUSKESMAS BONE KECAMATAN BONE KABUPATEN MUNA TAHUN 2022 - Ika Triani Sari; La Ode Muhamad Sety; Jumakil Jumakil (Endemis Journal, 2022)
Various countries are competing to be able to produce vaccines, because apart from dealing with the pandemic, vaccines will become a commodity that will be sought after and have high economic value. It is necessary to immediately carry out other effective interventions through vaccination efforts. This study aims to determine factors related to the practice of covid-19 vaccination in the community in the working area of the Bone Sub-district Health Center in Bone in 2022. This study used quantitative analytic with a cross sectional study approach. The sample in the study was 360 people. Sample selection using simple random sampling. The results showed that there was a significant relationship between knowledge (p value = 0.016 < 0.05) and the practice of Covid-19 vaccination, on the contrary there was no significant relationship between attitudes (p value = 0.390 > 0.05) and the practice of Covid-19 vaccination. 19. The conclusion of this study is that the knowledge variable has a significant relationship with the practice of vaccination in the community, while attitudes have no significant relationship with the practice of Covid-19 vaccination in the community in the working area of the Bone Health Center, Bone District in 2022.